UK Medical Research Council randomised, multicentre trial of interferon-alpha n1 for chronic myeloid leukaemia: improved survival irrespective of cytogenetic response. The UK Medical Research Council's Working Parties for Therapeutic Trials in Adult Leukaemia. - Allan, N; Richards, S; Shepherd, P (1995)
Interferon-alpha may be better than cytotoxic drugs in the long-term management of patients with chronic myeloid leukaemia (CML) in chronic phase. To test this possibility 587 patients with CML in chronic phase were randomly allocated to receive lymphoblastoid cell-line interferon-alpha n1 (IFN-alpha, n = 293) or chemotherapy with busulphan or hydroxyurea (no IFN-alpha, n = 294) as maintenance after initial induction treatment with cytotoxic drugs. There was a significant survival benefit for patients in the IFN-alpha arm when analysed on the basis of intention to treat (2p = 0.0009). The median survival for those allocated IFN-alpha was 61 months and no IFN-alpha was 41 months. Out of 269 patients with Philadelphia-positive CML in the IFN-alpha arm with at least 6 months follow-up, 211 were evaluable for haematological response: 145 (68%) achieved good responses (A+ or A type), 37 (18%) had partial responses (B type) and 29 (14%) had poor responses (C type). Patients with types A and B responses had a better survival than those in the no IFN-alpha arm; patients with type C responses had survival equivalent to the no IFN-alpha arm. Of these 269 patients, 26 of whom had not started IFN-alpha, 59 (22%) achieved a significant degree of cytogenetic response but 210 (78%) did not have a response. Cytogenetic responders survived significantly longer than non-responders and even non-responders survived longer than patients in the no IFN-alpha arm. Since cytogenetic non-responders had worse than average prognostic features, they may also benefit from IFN-alpha therapy. We conclude that treatment with IFN-alpha prolongs the survival of patients with CML; benefits of IFN-alpha are not confined to cytogenetic responders but may extend to most, if not all patients receiving IFN-alpha treatment; and cytogenetic response to IFN-alpha treatment identifies patients with a relatively good prognosis.